Functional differentiation as ideology of the (neo)colonial society - Gonçalves, Guilherme Leite (Thesis eleven, 2017)
This article discusses the ideological character of the notion of functional differentiation. According to Luhmann, the development of worldwide social differentiation (that is, the rise of the world society) leads to different regional developments and generates, through the inclusion/exclusion code, a division of the world between places where the functional differentiation operates appropriately and inappropriately. This paper argues, however, that functional differentiation is only readable as an ensemble of relations of power and ideological discourses. This subject is developed in light of theoretical approaches from the Marxist tradition and from postcolonial studies. Regarding the first, the functional differentiation is reread as an abstract and generic equality, which permits the material reproduction of regional inequality. This idea provides a background for discussing the ideological features of the functional differentiation which serves the dominant position of Western countries in the international arena since it enables the maintenance of a ruling ideology, according to which the world is differentiated between the ‘civilized’ West (where democracy performs positively) and the ‘uncivilized’ non-West (where democracy performs negatively).